Republic of Uzbekistan : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2008)
The Joint Staff Note (JNS) reports that Welfare Improvement Strategy (WIS) showed a commendable effort under the Poverty Reduction Strategy Paper (PRSP) in Uzbekistan. They stressed that implementation capacity within the government would have to be strengthened. Executive Directors agreed that strong implementation of the WIS and strengthening of WIS policy analysis and design would help reduce poverty and achieve the Millennium Development Goals (MDGs). They stressed the need for contributing toward the cost of programs and policies, establishing methods and institutions for its monitoring and evaluation, and providing technical assistance for raising the standards of WIS formulation and implementation.